Factors associated with the uncorrectable congenital heart disease in children with pulmonary arterial hypertension (Medical Journal of Indonesia, 2023)
BACKGROUND Pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD) is a common complication of uncorrected left-to-right shunt defects in acyanotic CHD and a frequent type of pulmonary hypertension in youth. The standards for operability in left-to-right shunts with increased pulmonary vascular resistance are not universally agreed upon. This study aimed to identify variables associated with uncorrectable lesion in children with PAH-CHD. METHODS This retrospective study used a database of all children who underwent cardiac catheterization at Sanglah Hospital, Bali, from May 2009 to April 2021. Pulmonary hypertension was defined as pulmonary artery pressure of >25 mmHg, while correctability was a fall of >20% in the pulmonary arterial resistance index (PARI) with final value of <6 WU/m2 when doing an acute vasoreactivity test using 100% oxygen. The analyses were carried out using SPSS software version 22.0 (IBM Corp., USA). RESULTS A total of 104 children were included. Cardiac catheterization showed that the uncorrectable group had a higher PARI (14.4 [8.88] WU/m2 versus 8.43 [3.85] WU/m2) and lower flow ratio (1.27 [0.83] versus 1.47 [0.77]) at baseline. In terms of correctability, pre-tricuspid lesions (OR = 0.05; 95% CI = 0.01–0.47; p = 0.01) and younger age group (OR = 0.32; 95% CI = 0.12–0.85; p = 0.01) were protective variables, whilst high baseline PARI (OR = 4.54; 95% CI = 1.64–12.57; p = 0.01) was unfavorable. CONCLUSIONS High baseline PARI was the most significant variable in predicting uncorrectable left-to-right shunt defects in PAH-CHD.